Moisture and fungal degradation in fibrous plaster. (10th March 2023) - Maundrill, Zoe C.; Dams, Barrie; Ansell, Martin; Henk, Daniel; Ezugwu, Emeka K.; Harney, Marion; Stewart, John; Ball, Richard J.
Highlights: Moisture and fungi degrade fibrous plaster. This is a major issue, emphasised by the Apollo theatre ceiling collapse in 2013. Fibrous plaster samples were subjected to moisture and fungal treatments for up to 2 years and degradation was evaluated. Submersion in water, wetting and drying and exposure to fungi over 2 years caused major reductions in mechanical properties. Peak ratio methods used on FTIR hessian fibre spectra identified different treatments as clusters in scatter plot results. FTIR and mechanical results can be used to determine causes of moisture or fungal degradation in fibrous plaster. Abstract: Fibrous plaster degradation has been a key concern over recent years, with ceiling failures occurring suddenly in historic buildings, including the Apollo theatre in 2013. This rigorous investigation explores fibrous plaster degradation through subjecting 290 specimens to a range of moisture and fungal-related treatment conditions over periods of up to two years and analysis using mechanical flexural tests, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Deoxyribonucleic Acid (DNA) sequencing. Using FTIR peak ratios from spectra of hessian fibres and mechanical tests in conjunction, an original methodology for identifying mechanisms and severity of fibrous plaster degradation through moisture and fungal exposure was developed. Results showed defined clusters for differing moisture and fungal treatments when two peak ratios are plotted together and compared with mechanical data. Fungal exposure over two years, water submersion and wetting and drying were particularly detrimental conditions for fibrous plaster. Fungal exposure resulted in degradation of cellulose bonds in hessian fibres, with defined clusters on the extreme left of peak ratio plots correlating with a pronounced reduction in fibrous plaster mean flexural strength of 51%. Fungal species Penicillium and Chaetomium were identified on test samples. Moisture affected plaster matrices significantly with wetting/drying and water submersion treatments resulting in a 71% reduction in mean flexural strength for unreinforced plaster, reducing to 26% with hessian-reinforced fibrous plaster. Many buildings containing fibrous plaster are listed and removal of material is often minimised - the high impact of this research stems from the ability to rapidly assess the mechanical integrity of a very small quantity of harvested historic hessian fibres using FTIR. Identifying the location of weakened fibres in a ceiling is highly important for effective restoration and conservation.